1994
DOI: 10.1093/ptj/74.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Are Incentive Spirometry, Intermittent Positive Pressure Breathing, and Deep Breathing Exercises Effective in the Prevention of Postoperative Pulmonary Complications After Upper Abdominal Surgery? A Systematic Overview and Meta-analysis

Abstract: Incentive spirometry and DBEX appear to be more effective than no physical therapy intervention in the prevention of postoperative pulmonary complications. There is no evidence to support a significant difference between any of the three modalities. [Thomas JA, McIntosh JM. Are incentive spirometry, intermittent positive pressure breathing, and deep breathing exercises effective in the prevention of postoperative pulmonary complications after upper abdominal surgery? a systematic overview and meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
0
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(100 citation statements)
references
References 21 publications
1
93
0
6
Order By: Relevance
“…As in many centers, respiratory physiotherapy and early mobilization strategies are being performed from the first day of surgery in our center. [17][18][19][20][21] We believe that our strict postoperative treatment including early mobilization, respiratory physiotherapy (incentive spirometry, chest physical therapy, and hyperinflation therapy), and postoperative analgesic techniques could be responsible for this lower incidence of early postoperative atelectasis.…”
Section: Discussionmentioning
confidence: 99%
“…As in many centers, respiratory physiotherapy and early mobilization strategies are being performed from the first day of surgery in our center. [17][18][19][20][21] We believe that our strict postoperative treatment including early mobilization, respiratory physiotherapy (incentive spirometry, chest physical therapy, and hyperinflation therapy), and postoperative analgesic techniques could be responsible for this lower incidence of early postoperative atelectasis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that teaching patients these techniques preoperatively reduces pulmonary complications to a greater extent than instructions given after surgery [75]. Deep-breathing exercises and incentive spirometry are equally effective in reducing the risk of PPCs, and the latter is less labor-intensive [76]. A review found that these techniques consistently reduced the relative risk of pulmonary complications by approximately 50% [77].…”
Section: Risk-reduction Interventionsmentioning
confidence: 99%
“…However, an IS seems to be more effective in improving respiratory muscle strength. Thomas and McIntosh [25] carried out a meta-analysis to analyze conflicting publications on the effectiveness of an IS, IPPB and deep breathing exercises in the prevention of postoperative pulmonary complications in patients who underwent upper abdominal operation. They concluded that deep breathing exercises and the use of an IS are most effective when compared to groups of patients who have not received any treatment.…”
Section: Physiotherapeutic Approach After Extubationmentioning
confidence: 99%